Doliche, Türkei. Siegelabdrücke aus dem Archiv von Doliche. Die Arbeiten des Jahres 2018 - Schreiber, Torben (e-Forschungsberichte des DAI, 2019)
The project “Archives and sealings from Asia Minor and adjacent regions” focusses mainly on the impressions of hellenistic and roman seals from ancient archives. In a first step, the inventory of the archive of Doliche will be reviewed. Until today, we know approximately 4000 impressions on document enclosures made of clay, which can be attributed to the city archive of Doliche. Since the archive burned down around the mid-3rd century AD, the project tries to re-contextualize the sealings by statistic and iconographic analysis. In a second step, the inventory of the Doliche archive will be compared with other archives within Asia Minor and adjoining regions in order to work out commonalities and differences.